Applications of cone beam computed tomography of the craniofacial structure in medical specialties. A review - Muñoz-Galván, Agustín (2022)
Cone-beam computed tomography (CBCT) of the craniofacial structure has demonstrated its usefulness in the dental area during the last decades, thus it has become a fundamental tool in the diagnosis, planning, and evaluation of treatment, and although it was not developed for the exclusive use in dentistry, as it is commonly considered, it is used in other areas such as medicine. It is specifically used in the head and neck area where different medical specialties interact, and at the same time these interact with dental specialties, so knowing the advantages of CBCT over different imaging technologies in the medical area is necessary. The purpose of this review was to describe the applications of observation, diagnosis, planning, and evolution of treatments using maxillofacial HSCT in different medical specialties. This work highlights the use of TCHC in different medical applications and highlights where it is most useful compared to other technologies.